The Influence of Standard Operating Procedures (SOP), Work Environment and Organizational Citizenship Behavior (OCB) on Employee Work Effectiveness (Study at PT. Perkebunan Nusantara III (PERSERO) Medan HR Operations Department) - Novita Ramayani Ritonga; Ainun Mardhiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee performance can be said to be good if activities within the company are carried out effectively and the results are in accordance with those set by the company. The purpose of this research is to examine how the work environment, Organizational Citizenship Behavior (OCB), and Standard Operating Procedures (SOP) influence the productivity of staff members in the HR operational department of PT. Perkebunan Nusantara III (Persero) Medan. Associative quantitative research methodology was used in this research. The population of this study consisted of 45 respondents who worked in the HR Operations Department of PT. Perkebunan Nusantara III (Persero) Medan. The research results show that at an influence level of 65.3%, the variables Organizational Citizenship Behavior (OCB), Work Environment, and Standard Operating Procedures (SOP) simultaneously influence employee work effectiveness. The remaining 34.7% of the workforce is influenced by factors not covered in this research.